Evaluasi Kinerja Likuiditas, Aktivitas dan Profitabilitas (Studi Kasus Di CV. Unggul Perdana Organik Blora) - Mateus Dian Sanjaya; Maria Rio Rita (EBBANK, 2017)
This study aims to analyze company performance on CV Unggul Perdana Organik (CV UPO) Blora through financial statement analysis. Previous research has many that analyze the financial performance in large companies, but not many in SME companies. During the time, assessment of CV UPO in company's performance only based on the benefits generated. The analysis is done by comparing the company's financial ratios for five years. We find that the liquidity of CV UPO has been decrease in the last two years when compared with the existing average. For activity ratios, CV UPO has been in good position because the average for the last three years inventories less than the average inventories for five years.Meanwhile, CV UPO has been quite effective to manage fixed assets and total assets, due in the last two years those ratios are increase. For profitability ratios, compare with the average value available, the ability of CV UPO to generate net profit from existing sales in the last two years is decreased, while the ability of CV UPO in net profit outcome of total cost owned increased in the last two years.